Osteotomy Correction Angle Cut‐off Points Can Guide the Operation to Prevent a Significant Decrease in Patella Height - Renjie Chen; Chenghao Yu; Haining Peng; Jinli Chen; Yi Zhang; Tengbo Yu (Orthopaedic Surgery, 2024)
Objective Patients who undergo a biplanar ascending medial open‐wedge high tibial osteotomy with an excessive correction angle might experience patella infera and even knee pain after surgery. The purpose of this study was to identify the cut‐off points for the degree of knee varus correction of open‐wedge high tibial osteotomy, which is related to the symptomatic patellar position change. Methods This retrospective study included 124 patients (mean age 61.69 ± 6.28 years; 78 women, 46 men) with varying degrees of varus knee osteoarthritis. All patients had undergone standard biplanar medial open‐wedge high tibial osteotomy. They were divided into nine groups according to the change in hip–knee–ankle angle. Plain radiographs and three‐dimensional CT images were obtained preoperatively and 18 months postoperatively. Patellar height was assessed using the Caton–Deschamps index, the Insall–Salvati index, and the Blackburne–Peel index. The patellofemoral index and patellar tilt were used to evaluate the degree of horizontal displacement of the patella. The varus correction, medial–proximal tibial angles, joint line convergence angles, and hip–knee–ankle angles were also measured. The subjective score was evaluated using the Western Ontario and McMaster Universities osteoarthritis index (WOMAC). Results There were significant changes in patella indexes in each group after surgery, among which there was no significant difference in patellar height changes for Groups A to F (p > 0.05), which were significantly lower than those in Group G, H, and I (p < 0.001). The patellar tilt and patellofemoral index also followed the same trend. The improvement in WOMAC scores for Groups G, H, and I was also significantly less for Groups A to F (p < 0.001). Conclusion The patellar height, patellar tilt, and patellofemoral index all changed significantly in parallel with increasing degrees of osteotomy correction. The cut‐off points for correction angle are 12.5° to 13.4°. When the correction angle is larger than this range, the patellar position can be significantly affected. Postoperative patellofemoral joint pain may be related to the changes in patella position.